Teacher strategies for developing qur'anic reading skills in sixth grade: A case study at sdn 1 tempursari - Santi Mubarokah; Amir Mukminin; Mohammad Abdul Munjid; Edi Susanto; Mohammad Farhan Zeb Khan (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2025)
This research aims to identify and analyze various approaches used by Islamic Religious Education teachers in improving Qur'an reading skills among 6th-grade students at SDN 1 Tempursari in the 2024/2025 academic year. The study employs a descriptive qualitative methodology, collecting data through participatory observation, in-depth interviews, and document analysis. Research participants include Islamic Religious Education teachers, school principals, and 6th-grade students. The research findings reveal that strategies implemented by Islamic Religious Education teachers include: (1) application of the Iqro' method adapted to each student's proficiency level; (2) utilization of audio-visual learning media and digital applications for Qur'an learning; (3) organization of peer tutoring study groups; (4) implementation of regular Qur'an recitation activities for 15 minutes before Islamic Religious Education lessons begin; and (5) establishment of collaboration with parents and local Qur'anic Education Centers (TPQ) in the school environment. Several factors supporting the success of these strategies include supportive school policies, availability of adequate facilities and infrastructure, and active parental involvement. Meanwhile, factors hindering strategy implementation include limited time allocated for Islamic Religious Education learning, diversity in students' basic abilities, and minimal habituation of Qur'an reading in the family environment. Based on the research results, several recommendations are proposed including increasing time allocation for Qur'an learning, developing religious extracurricular programs, and optimizing parents' role in accompanying children learning to read the Qur'an at home.